2015
DOI: 10.22256/pubvet.v16n3.1281
|View full text |Cite
|
Sign up to set email alerts
|

Utilização de coleópteros na preparação de material osteológico

Abstract: ResumoEste trabalho tem como finalidade divulgar a utilização de Dermestes maculatus na preparação de material osteológico de diferentes espécies animais e, ao mesmo tempo, contribuir para a diversificação da coleção osteológica da Seção de Anatomia da UENF. Seis animais de diferentes espécies tiveram seus esqueletos limpos pelos insetos. O procedimento de limpeza completa foi obtido em diferentes períodos de tempo e mantinha uma relação direta com o número de larvas e insetos adultos presentes nas colônias. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
3
0
2
Order By: Relevance
“…According to Hefti and collaborators (13) , it is impossible to predetermine the processing time because many variables directly influence the result, such as the size and composition of the beetle population, available food, temperature, and light incidence on the breeding sites. In the study by Rodrigues et al (6) , where Dermestes were used to clean whole skeletons of some animals, a processing time of four months was obtained for an iguana, one month for a pig and a ferret, 20 days for the common ground dove, and 10 days for a bat and an owl. Although many variables can interfere with the final result, it is noted that compared to Dermestes, the lesser mealworms showed an 80% reduction in the time required to clean an owl skeleton, taking only two days for completion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Hefti and collaborators (13) , it is impossible to predetermine the processing time because many variables directly influence the result, such as the size and composition of the beetle population, available food, temperature, and light incidence on the breeding sites. In the study by Rodrigues et al (6) , where Dermestes were used to clean whole skeletons of some animals, a processing time of four months was obtained for an iguana, one month for a pig and a ferret, 20 days for the common ground dove, and 10 days for a bat and an owl. Although many variables can interfere with the final result, it is noted that compared to Dermestes, the lesser mealworms showed an 80% reduction in the time required to clean an owl skeleton, taking only two days for completion.…”
Section: Resultsmentioning
confidence: 99%
“…Dermestes maculatus is a widespread beetle that feeds on dead animal carcasses (4) . This species has been reproduced in laboratories for decades for preparing biological materials (5) because it produces less unpleasant odors when compared to other maceration processes and keeps the specimens fully articulated during the cleaning process (6) . However, when applying this method to the preparation of bat skulls, Oliveira (7) observed that Dermestes caused structural damage to some pieces due to the consumption of bone extract, even in the presence of soft tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The limitations of controlled maceration with dermestids are related to the need to maintain the colony at a suitable size and to control temperature oscillations, which is a determinant factor for the efficiency and especially for the duration of the process (Sullivan & Romney, 1999;Rodrigues et al, 2012). According to Köb (2006), the ideal temperature to maintain a colony of dermestids is around 25°C.…”
Section: Discussionmentioning
confidence: 99%
“…De acordo com Hefti e colaboradores (13) , não é possível pré-determinar o tempo de processamento pois existem muitas variáveis que influenciam diretamente no resultado final, tais como, o tamanho e a composição da população de besouros, alimentação disponível, temperatura e incidência de luz sobre os criadouros. No estudo realizado por Rodrigues et al (6) , onde foram utilizados Dermestes para limpar esqueletos inteiros de alguns animais, foi obtido um tempo de processamento de quatro meses para uma iguana, um mês para um suíno e para um ferret, vinte dias para a rolinha e dez dias para um morcego e uma coruja. Apesar de existirem muitas variáveis que podem interferir no resultado final, nota-se que, quando comparado com o Dermestes, os cascudinhos apresentaram redução de 80% no tempo necessário para limpar um esqueleto de coruja, demorando apenas dois dias para completar a limpeza.…”
Section: Estes Mesmos Autores Recomendam Que O Local Utilizado Para A...unclassified
“…O Dermestes maculatus é um besouro com ampla dispersão geográfica que se alimenta de carcaças de animais mortos (4) . Esta espécie vem sendo reproduzida em laboratórios há décadas com a finalidade de preparar materiais biológicos (5) , isso porque estes insetos produzem menos odores desagradáveis, quando comparados com outros processos de maceração, além de manter os exemplares totalmente articulados durante o processo de limpeza (6) . No entanto, ao aplicar este método na preparação de crânios de morcegos, Oliveira (7) observou que os Dermestes causaram danos estruturais em algumas peças devido ao consumo do extrato ósseo, mesmo na presença de tecidos moles.…”
Section: Introductionunclassified